2017
DOI: 10.1007/s11548-017-1533-5
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive, multi-port approach to the lateral skull base: a first in vitro evaluation

Abstract: The presented system allows the planning and drilling of multiple minimally invasive canals at the lateral skull base. Further studies are required to reduce the drilling error and evaluate the clinical application of the system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Further integration of intraoperative imaging devices will drastically reduce the time needed for pre- and intraoperative imaging and image processing. To introduce a complete robotic cochlear implantation approach, we are currently developing and investigating solutions for robotic inner ear access, robotic electrode insertion, multi-port scenarios [29], narrower drills (i.e. 1mm to 1.4 mm) with integrated monitoring electrodes and ultimately robotics compliant CI implant technology.…”
Section: Discussionmentioning
confidence: 99%
“…Further integration of intraoperative imaging devices will drastically reduce the time needed for pre- and intraoperative imaging and image processing. To introduce a complete robotic cochlear implantation approach, we are currently developing and investigating solutions for robotic inner ear access, robotic electrode insertion, multi-port scenarios [29], narrower drills (i.e. 1mm to 1.4 mm) with integrated monitoring electrodes and ultimately robotics compliant CI implant technology.…”
Section: Discussionmentioning
confidence: 99%
“…To resolve the limitations to simultaneous visualization and manipulation assistance requirements that are imposed by a single drill tunnel to the cochlea, a multiport approach was investigated for its suitability and feasibility for the RCI approach. It has previously been shown that planning multiple trajectories with adequate safety clearance despite anatomical variations was feasible [5][6][7]; as was the drilling of trajectories with the adequate accuracy [8].…”
Section: Introductionmentioning
confidence: 99%